180 Evaluation of soluble concentrated yeast product on sow and litter performance - Thompson, Robyn (J Anim Sci, 2019)
Two hundred and forty sows (Camborough, PIC, Hendersonville, TN) were started on study at 35 d post-breeding through lactation to determine the effects of soluble concentrated yeast product (Celmanax SCP, Arm and Hammer, Princeton, NJ) on sow and litter performance. Sows were fed their respective dietary treatments: 1) Control diet gestation x control diet lactation; 2) 0.01% Celmanax SCP in gestation x control diet lactation; 3) Control diet gestation x 0.02% Celmanax SCP in lactation; and 4) 0.01% Celmanax SCP in gestation x 0.02% Celmanax SCP in lactation. All diets were formulated to meet or exceed NRC (2012) requirements and contained a feed disinfectant. Sows were allowed ad libitum access to feed and water in lactation. Litters were weighed after cross-fostering, 48 h post-farrow (after litter adjustments and cross-fostering) and at weaning. Sows were weighed entering farrowing and at weaning. Data were analyzed as a randomized complete parity block using PROC MIXED of SAS with sow as the experimental unit, treatment as a fixed effect, and parity as a random effect. There were detectable levels of fumonisin (2 ppm), vomitoxin (1.3 ppm) and zearalenone (243 ppb). There were no differences in sow feed intake or body weight loss (P > 0.10). There was a significant difference in treatments 1, 2, 3 and 4 for days between wean to estrus (5.99, 5.12, 4.90, 4.49; P = 0.01) and percent bred within 7 d (86.53, 97.06, 97.85, 100.00; P = 0.01), respectively. Average piglet wean weights (kg) were 5.82, 5.87, 5.93, 6.01; P = 0.02 for treatments 1, 2, 3 and 4 respectively. Furthermore, there were no responses in piglet average daily gain or mortality (P > 0.10). The feeding of the soluble yeast product to sows does appear to improve subsequent breeding and litter performance.